Designing Learning Outcomes for Handoff Teaching of Medical Students Using Group Concept Mapping: Findings From a Multicountry European Study. (July 2015) - Hynes, Helen; Stoyanov, Slavi; Drachsler, Hendrik; Maher, Bridget; Orrego, Carola; Stieger, Lina; Druener, Susanne; Sopka, Sasa; Schröder, Hanna; Henn, Patrick
Abstract : Purpose: To develop, by consultation with an expert group, agreed learning outcomes for the teaching of handoff to medical students using group concept mapping. Method: In 2013, the authors used group concept mapping, a structured mixed-methods approach, applying both quantitative and qualitative measures to identify an expert group's common understanding about the learning outcomes for training medical students in handoff. Participants from four European countries generated and sorted ideas, then rated generated themes by importance and difficulty to achieve. The research team applied multidimensional scaling and hierarchical cluster analysis to analyze the themes. Results: Of 127 experts invited, 45 contributed to the brainstorming session. Twenty-two of the 45 (48%) completed pruning, sorting, and rating phases. They identified 10 themes with which to select learning outcomes and operationally define them to form a basis for a curriculum on handoff training. The themes "Being able to perform handoff accurately" and "Demonstrate proficiency in handoff in workplace" were rated as most important. "Demonstrate proficiency in handoff in simulation" and "Engage with colleagues, patients, and carers" were rated most difficult to achieve. Conclusions: The study identified expert consensus for designing learning outcomes for handoff training for medical students. Those outcomes considered most important were among those considered most difficult to achieve. There is an urgent need to address the preparation of newly qualified doctors to be proficient in handoff at the point of graduation; otherwise, this is a latent error within health care systems. This is a first step in this process.